The Heights : anatomy of a skyscraper - Ascher, Kate.; Vroman, Rob. (New York : Penguin Books, 2011)
A gorgeous graphic tour of the inner workings of skyscrapers$1 (Bfrom the author of The Works. Indispensable and unforgettable, The Heights is the ultimate guide to the way skyscrapers work$1 (Bfrom the bases of their foundations to the peaks of their spires. With skyscrapers becoming essential elements of urban life, there has never been a greater need for understanding and embracing these complex structures. Using innovative illustrations to tackle the vast complexity of these buildings, The Heights explores with remarkable insight every aspect of designing, building, and maintaining a modern skyscraper, as well as the individuals who build and maintain these architectural cathedrals. In the process, The Heights provides a remarkable snapshot of urban life at the dawn of the twenty-first century.s
1. Introduction 2. Building it. Design -- 3. Living in it -- 4. Supporting it. -- 5. Dreaming it -- Acknowledgements -- Credits -- Index.
Includes index.
Keywords: SKYSCRAPERS